Assessing the impact of supervised interval training on cardiovascular autonomic neuropathy in type 2 diabetes patients - Stirane, Laura; Stirans, Karlis; Pahirko, Leonora; Mednieks, Janis; Ostrovska, Karina; Kļavina, Aija; Selavo, Leo; Sokolovska, Jelizaveta (Physiological reports, 2025)
This post hoc analysis of the “Healthy walk” study evaluated the effect of interval walking training on cardiovascular autonomic neuropathy (CAN) in type 2 diabetes (T2D) patients. At baseline, 64 T2D patients underwent tilt table testing with autonomic reflex tests: heart rate responses to the Valsalva maneuver, deep breathing, and standing, and blood pressure responses to standing and sustained handgrip, using the Ewing score. Fifty‐six participants were allocated to an interval training (IT) group and control group. The IT group completed supervised interval walking training three times weekly for 60 min over 4 months, while the control group received physical activity education. Twenty‐four participants in the IT group and 30 in the control group completed the study. The primary endpoint of this post hoc analysis was the change in Ewing score. CAN was detected in 42 patients (66%), mean Ewing score of 2.7 ± 0.72. Those with CAN, 16 were in the IT group and 19 in the control group. Both groups showed a significant reduction in Ewing scores (IT: from 2.5 to 1.77, p = 0.003; control: from 2.72 to 1.91, p = 0.001). Interval walking training and physical activity education both reduce CAN severity in T2D patients.